S-Know Microlearning: Integral Part of Knowledge Management for Employee Training in the Indonesian Banking Industry - Indah Resti Fauzi; Herbert Siregar; Yudi Ahmad Hambali; Samialloi Nusratullo; Rasim Rasim (Jurnal Nasional Teknologi dan Sistem Informasi, 2025)
The lack of integrated and easily accessible knowledge-sharing platforms within organizations, especially in the banking industry, has led to challenges in preserving institutional expertise and supporting effective employee training. S-Know (Smart Knowledge) is a web-based knowledge management system developed to address this issue by facilitating the storage, management, and distribution of organizational information. It offers features such as learning paths, learning modules, quizzes, and discussion forums to promote structured collaboration and self-directed learning among employees. The content is designed using a microlearning approach to ensure better comprehension and relevance to new staff training. The development of S-Know followed the Knowledge Management System Life Cycle (KMSLC), encompassing stages of knowledge capture, system design, implementation, and evaluation, each tailored to align with real organizational needs. Technically, S-Know leverages the Laravel framework for scalability and flexibility, with black box testing used to evaluate system functionality against user requirements. Test results and user interviews confirmed that all core features performed effectively and supported the intended goals. Overall, S-Know shows strong potential as a strategic and adaptive platform for knowledge management that can enhance human resource development and support sustainable organizational knowledge. To further support its growth and long-term value, future development may focus on encouraging greater user participation in knowledge sharing and improving accessibility, especially through integration with mobile platforms.